Imaginación artificial, imagen poshumana y pensamiento humano (Monográfico) - Català Domènech, Josep Maria (2024)
The appearance of AI image generators within artificial intelligence suggests the existence of an artificial imagination that drives us to reconsider the relationship between image and thought. Artificial imagination points to a new image of thought, that suits the growing complexity of contemporary reality. To understand the ontology of artificial imagination, which is related to two types of unconscious, the machinic and the human, some of the concepts proposed by Deleuze and Guattari are useful, especially the one related to “abstract machines”. The basic parameters of these new images require reconsidering psychosocial and philosophical areas that are affected by the presence of new technological devices that have appeared within the last phases of capitalism.